Microplastics in sub-surface waters of the Arctic Central Basin. (May 2018) - Kanhai, La Daana K.; Gårdfeldt, Katarina; Lyashevska, Olga; Hassellöv, Martin; Thompson, Richard C.; O'Connor, Ian
Abstract: Polar oceans, though remote in location, are not immune to the accumulation of plastic debris. The present study, investigated for the first time, the abundance, distribution and composition of microplastics in sub-surface waters of the Arctic Central Basin. Microplastic sampling was carried out using the bow water system of icebreaker Oden (single depth: 8.5 m) and CTD rosette sampler (multiple depths: 8–4369 m). Potential microplastics were isolated and analysed using Fourier Transform Infrared Spectroscopy (FT-IR). Bow water sampling revealed that the median microplastic abundance in near surface waters of the Polar Mixed Layer (PML) was 0.7 particles m −3 . Regarding the vertical distribution of microplastics in the ACB, microplastic abundance (particles m −3 ) in the different water masses was as follows: Polar Mixed Layer (0–375) > Deep and bottom waters (0–104) > Atlantic water (0–95) > Halocline i.e. Atlantic or Pacific (0–83). Highlights: Microplastics discovered in sub-surface waters (8–4369 m) of Arctic Central Basin. Predominance of fibrous microplastics and the synthetic polymer polyester Highest microplastic abundance nearer the periphery of the Arctic Central Basin Water layer with highest microplastic abundance was the Polar Mixed Layer.